Learning Discipline, Achievement Motivation, Intellectual Intelligence, and Teachers' Pedagogical Competence on Students' Science Learning Outcomes - Ni Ketut Sulastri; Ni Luh Gede Erni Sulindawati; Ni Wayan Sukerti (Universitas Pendidikan Ganesha, 2026)
Science learning outcomes have not yet achieved optimal levels, as reflected in students’ low learning motivation and engagement. This condition is associated with internal student factors namely learning discipline, achievement motivation, and intellectual intelligence as well as an external factor represented by teachers’ pedagogical competence. This study aims to examine the contribution of these four factors to science learning outcomes, both partially and simultaneously. A quantitative approach employing an ex post facto research design was utilized. The study population consisted of 235 eighth-grade students, from which 148 participants were selected using the Krejcie and Morgan sampling table. Data were collected through Likert-scale questionnaires and documentation of students’ end-of-semester summative assessment scores. Data analysis involved simple regression, multiple linear regression, and partial correlation techniques after meeting the required statistical assumptions. The findings indicate that learning discipline, achievement motivation, intellectual intelligence, and teachers’ pedagogical competence each make significant contributions to science learning outcomes, both individually and collectively. These results underscore the importance of strengthening students’ internal learning factors in alignment with the continuous enhancement of teachers’ pedagogical competence. The study implies that structured pedagogical interventions are essential to optimize science learning outcomes.